RETRACTED: State regulation of the use of ESG methodology - Misnikova Lyudmila; Aleksandrov Igor; Parshukov Aleksey; Maksina Svetlana; Ilina Victoria; Terentyev Alexey; Ol Ekaterina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001